STRATEGIC PLANNING OF ACTIVITIES IN A TOURIST ORGANIZATION (Development Service Industry Management, 2023)
The current state of war in Ukraine is characterized by the decline of the tourism industry in most regions, the curtailment of social programs in this direction, the loss of positive trends and dynamics of the development of family and supporting industries, the low competitiveness of tourist services and the pace of economic development in general. The purpose of the study is to determine the features of strategic planning in tourism organizations in modern conditions and to identify factors influencing its formation.The sequence of choosing a general strategy for the development of a tourist organization based on strategic planning is substantiated. The composition and nature of the main influencing factors on the process of strategic planning in the tourism organization were studied:- the state of supporting industries and the tourism industry, the position of the tourist organization under investigation;- goals of the tourist organization;- interests and attitude to business of top management;- staff qualification;- financial support of the business entity;- obligations of the tourist organization regarding previous strategies.- the degree of dependence on the factors of direct and indirect influence of the external environment.- time factor.Based on the results of the analysis, it was concluded that the organization of an effective strategic planning mechanism will help not only to form real goals, but also to ensure their systematic achievement.
Keywords: strategic planning; tourism organization; development strategy; competitive advantage; life cycle; costs